Vodnik skozi postopke pri analizi ankete s statističnim programom SPSS: 1. del: Priprava ankete in podatkovne datoteke - Božović, Dragana; Tepeh, Aleksandra; Radić, Gordana (University of Maribor Press, 2026)
Guide to Survey Analysis Procedures Using the SPSS Statistical Program – Part 1. The publication Guide to Survey Analysis Procedures Using the SPSS Statistical Program – Part 1 is a practical resource designed for beginning users of SPSS. It focuses on the essential early stages of the research process that precede any statistical analysis: understanding statistical units and variables, planning the research design, constructing a questionnaire, and preparing the data file. It leads the reader step by step through questionnaire development, coding and organizing variables, importing and structuring data, and using the core components of the SPSS environment. The guide emphasizes clear explanations, illustrative examples, and practical advice that help readers establish a reliable data foundation for subsequent analyses. It is conceived as a hands-on tool for users who need clear and useful instructions for working with SPSS in the context of data handling and survey analysis.